Pengembangan Aplikasi Data Warehouse Prestasi Mahasiswa (Studi Pada: Fakultas Ilmu Komputer Universitas Brawijaya) - Sausan Zahrah; Issa Arwani; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Study program accreditation is done every five years. In the accreditation process, there are several parameters used for accreditation assessment, including student achievement, one of which is seen from the aspect of achievement. At the Faculty of Computer Science, student achievement data is stored by the Student Affairs Section. Whereas student academic data is stored by the Academic Section. In recapitulating achievement and academic data, the study program at the Faculty of Computer Science obtains data from two different sources, they are the Student Affairs Section and Academic Section. To simplify the process of recapitulating data from the two sources, a data warehouse is needed so that data from different sources can be accessed at the same time. In building a data warehouse, the design phase that has been done refers to the Nine Step Methodology. From the design and implementation phase, it produced 6 dimension tables with 3 fact tables, they are the fact table Achievement, Graduates and Active Students. Then, a validation test is performed which results in a valid status in all test cases, and then the ETL performance testing in terms of time is done with the average time required for the execution of the ETL process is Â± 11 seconds with a total amount of 32,746 data.